Pengaruh Berbagai Konsentrasi Eco Enzyme dan Pinching Terhadap Pertumbuhan dan Pembungaan Tanaman Pacar Air (Impatiens hawkeri Bull) Pada Vertical Pipe - Poppy, Poppy Rizky Damayanti; Udayana, Cicik; Sitawati, Sitawati (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Brawijaya, 2023)
New Guinea Impatiens (Impatiens hawkeri Bull) is a plant with beautiful crown with a lot varieties of colors that has potentially used as an ornamental plant. Production is influenced by many factors such as knowledge about technologies in cultivation techniques. The cultivation techniques are being implementation a vertical system using paralon pipes and application of eco enzyme and pinching treatment. The aim of this research is to learn the interaction between application of various concentrations of eco enzyme and pinching methods on the growth and flowering of New Guinea Impatiens. The research was conducted from December 2021 to April 2022 at greenhouse on the experimental area of the Faculty of Agriculture, Brawijaya University, Jatimulyo Village, Lowokwaru District, Malang City, East Java. This research used a Randomized Complete Block Design (RCBD) with two factors and 3 repetition. The first factor is concentration of eco enzyme and the second factor is pinching treatment. Observations were made on plant growth and flower production. The data which is obtained from the observations were analyzed using ANOVA with the rate of 5%, if there is a significant effect, a further test using the Honest Significant Difference (HSD) with the rate of 5%. The results showed that there is significant interaction occurred in the application of eco enzyme and pinching treatment in all observation variables. The highest result of New Guinea Impatiens’s growth and flower production was obtained in the eco enzyme treatment with concentration of 10 ml.l-1 and double pinching. Number of flowers of New Guinea Impatiens in that treatment increased 2.95 times compared to without eco enzyme and without pinching. The time of flower appear of Impatiens hawkeri Bull showed a significant interaction with the application of eco enzyme with concentration of 5 ml.l-1 and double pinching treatment because the average time of flowers appear is 9.44 days slower than the treatment without eco enzyme and without pinching.